Analisis Pengembangan Strategi Pemasaran Produk Yourdayflower Dalam Meningkatkan Penjualan Menggunakan Metode SWOT - Rahmad Akbar; T.Yoga winanda; Dzulhijjahyetti; Merlia Rahmayani; Harmi Yelmi (Politeknik Kampar, 2020)
Abstract- Yourdayflower is an industry that makes bucket products. the problem faced by Yourdayflower is the declining level of sales. The purpose of the research conducted is to determine the advantages of competitors by knowing strengths, weaknesses, opportunities, threats, and designing marketing strategies in an effort to increase sales. The results obtained from processing the SWOT calculation are Yourdayflower's strengths are attractive product designs, Yourdayflower's weaknesses are the product variations that are few in comparison, the opportunities that the company has are high consumer loyalty to Yourdayflower products and the threat from this company is the emergence of similar products and obtained several marketing strategies from the SWOT matrix.Keywords: Yourdayflower, SWOT.